Influence of sulphate on synthesis of Nd:Y2O3 powders via coprecipitation route and fabrication of transparent ceramics. (February 2013) - Huang, Z.; Guo, W.; Fei, B. J.; Li, J. T.; Cao, Y. G.
Abstract : Neodymium doped yttrium carbonate precursors were synthesised via a normal strike coprecipitation route, employing NH4 HCO3 as precipitant and (NH4 )2 SO4 as surfactant. Nd:Y2 O3 powders were obtained through calcining the precursors at 1100°C for 3 h. The precursors, Nd:Y2 O3 powders and ceramics samples were characterised by means of several analytic techniques, such as differential thermal and thermogravimetric analysis, Fourier transform infrared, X-ray powder diffraction, TEM and SEM. The as synthesised precursors were amorphous, which gradually changed from agglomeration to needle-like shape along with the increase in (NH4 )2 SO4 . The Nd:Y2 O3 powders derived from needle shaped precursors exhibited good dispersion with mean particle sizes at ∼50 nm. The well dispersed Nd:Y2 O3 powders also showed good sinterability, and the corresponding sintered ceramics samples were highly transparent.